2021
DOI: 10.1021/jacs.1c02245
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Molecular Interaction Enabled Separation of Large-Diameter Semiconducting Single-Walled Carbon Nanotubes

Abstract: Semiconducting single-walled carbon nanotubes (s-SWCNTs) with a diameter of around 1.0–1.5 nm, which present bandgaps comparable to silicon, are highly desired for electronic applications. Therefore, the preparation of s-SWCNTs of such diameters has been attracting great attention. The inner surface of SWCNTs has a suitable curvature and large contacting area, which is attractive in host–guest chemistry triggered by electron transfer. Here we reported a strategy of host–guest molecular interaction between SWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 93 publications
0
61
1
Order By: Relevance
“…As such, there are very few examples describing the successful encapsulation of POMs within single‐walled carbon nanotubes (SWNTs), and these primarily focus on the use of stable, plenary polyoxotungstates. [ 46 , 47 , 48 , 49 ] We recently reported that [PW 12 O 40 ] 3− ( PW 12 ) and [P 2 W 18 O 62 ] 6− ( P 2 W 18 ) spontaneously fill SWNTs under aqueous conditions, a process driven by an in situ redox reaction between the POMs and the SWNTs. [50] The resultant hybrid materials ( PW 12 @SWNT and P 2 W 18 @SWNT respectively, where @ indicates that the POMs are immobilized within the cavities of the SWNTs) exhibited reversible redox chemistry and were stable under harsh conditions and long‐term electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…As such, there are very few examples describing the successful encapsulation of POMs within single‐walled carbon nanotubes (SWNTs), and these primarily focus on the use of stable, plenary polyoxotungstates. [ 46 , 47 , 48 , 49 ] We recently reported that [PW 12 O 40 ] 3− ( PW 12 ) and [P 2 W 18 O 62 ] 6− ( P 2 W 18 ) spontaneously fill SWNTs under aqueous conditions, a process driven by an in situ redox reaction between the POMs and the SWNTs. [50] The resultant hybrid materials ( PW 12 @SWNT and P 2 W 18 @SWNT respectively, where @ indicates that the POMs are immobilized within the cavities of the SWNTs) exhibited reversible redox chemistry and were stable under harsh conditions and long‐term electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between PTA and SWCNTs were reported. 56,57 These features make PTA a potential dopant for the SWCNT TCFs.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe a notable color change to dark blue aer adding subnanometer CoMo-SWCNTs into {PW 12 } aqueous solution, which is different from the phenomenon observed in previous reports when encapsulating {PW 12 } into large-diameter (1-2 nm) SWCNTs to form heteropoly blues. 70,73 It was further found that there was no obvious shi for the G band of {PW 12 }-out-SWCNTs, compared with that of pristine SWCNTs (Fig. S3 †).…”
Section: Assembly Of Polyoxometalate Clusters On Subnanometer Swcntsmentioning
confidence: 96%
“…[70][71][72] We demonstrated that the formation of electron donor-acceptor systems composed of SWCNTs and encapsulated polyoxometalates is effective to modulate the interaction of inter-tubes, thus selectively extracting largediameter semiconducting SWCNTs. 73,74 The adaptability in chemical synthesis provides a wide variety of customized polyoxometalates with tunable redox potentials, which enables precise modulation of the electronic properties of SWCNTs.…”
Section: Introductionmentioning
confidence: 99%